Product Testing of Extruded Cookies Made from Local Deworming Medicine - ode, Nirmala; Salakory, Melianus; Lasaiba, Mohammad Amin (Jurnal Pendidikan Geografi Unpatti, 2022)
Hantakan Subdistrict is one of the sub-districts in Hulu Sungai Tengah Regency that experienced flash floods in 2021. The flood event repeats it self every rainy season and result in floofing. The purpose of this study is to analyze the level of flood vulnerability in Hantakan District, Hulu Sungai Tengah Regency. The study was carried out in Hantakan Subdistrict as a population and using a presumption map modeling flood vulnerability as a sample. The analysis method used is by scoring on each flood vulnerability parameter and testing the accuracy of flood vulnerability presumption modeling data for making flood vulnerability maps. With the flood vulnerability map, people can fin out places that are prone to flooding and can be alert if there is a flood.